THE SEASONAL ABANDANCE , PERCENTAGE OF INFESAATION AND SEVERTY OF VEGETABLES LEAVES MINER Liriomyza sativa B. (Diptera : Agromyzidae)IN THE CUCUMBER FOR AUTUMN SEASON IN BAGHDAD - SH. A. ABBAS; R. S. AL-Jorany (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in the fields of plant protection department / projects of integrated management and plant protection /Abu Graib ,to determine the seasonal abandane, severity , and percentage of infestation for vegetables leaves miner Liriomyza sativae B. (Diptera :Agromyzidae) in cucumber Cucumis sativus for the autumn season 2016. The percentage of plants infestation was 20% and for leaves 4.1% in the first week of September , while severity of infestation was 0.16% . In the third week of October 2016 the percentage of infestation was increased progressively up to 93.3% and 44.7% in the plants and leaves respectively, and  the severity of infestation was 2.45 in the same week (That means 70% of leaves contain 6 -10 miner /leaf . Weight of fruits decreased from 505 gm/10 of plants in the second week of October 2016 to 180 gm/10 plants in the second week , When the number of miner incraside for 9.5 to 11.6 miner /leave . Correlation Analysis showed inverse relationship between fruits weight and number of miner/leaves with correlation (r = - 0.64 ) . The relationship between the population density of adults and feeding punctures /leave was positive with correlation(r=0.59)